Ramadelas Tree as a Potent Source of Antioxidant Herbal Tea: Pohon Ramadelas sebagai Sumber Herbal Teh Antioksidan yang Kuat - Rumbouw, Muna; Mattinahoru, Johan; Latumahina, Fransina Sarah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Antioxidants play a crucial role in neutralizing free radicals, which are linked to cellular damage and the onset of various chronic diseases. Specific Background: The exploration of natural antioxidant sources, particularly from endemic Indonesian flora, is gaining momentum due to their therapeutic and ecological value. Knowledge Gap: However, limited research exists on indigenous plants from East Seram, particularly those with traditional use in herbal beverages. Aims: This study investigates the botanical characteristics, processing methods, and antioxidant potential of the Ramadelas tree (Camellia sinensis var. assamica), a culturally significant plant in East Seram. Results: Phytochemical analysis revealed that Ramadelas tea exhibits strong antioxidant activity, with an IC50 value of 87.856 μg/mL. Novelty: This is the first scientific documentation linking the traditional practice of Ramadelas tea consumption with its quantifiable antioxidant capacity. The plant’s cultural narrative—hospitality through “rama” and delicious taste—aligns with its biochemical potential to support health. Implications: These findings support the use of Ramadelas tea as a functional beverage and contribute to the valorization of local biodiversity for nutraceutical development and ethnobotanical conservation. Highlights: Strong antioxidant with IC50 value of 87.856 μg/mL. Traditionally used herbal tea with cultural significance. Potential for functional beverage and health promotion. Keywords: Ramadelas Tree, Antioxidant Activity, Herbal Tea, Free Radicals, East Seram